Über Zusammenhängen des Raumes von Stützelementen - Urbonas, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Г. Урбонас, О связностях в пространстве опорных элементовA. Urbonas, Apie atraminių elementų erdvės sąryšius